1994
DOI: 10.1111/j.1432-1033.1994.tb19022.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of the human biliary glycoprotein gene, a CEA gene family member down‐regulated in colorectal carcinomas

Abstract: Biliary glycoprotein (BGP) isoantigens are derived by alternative splicing from a single gene and are the human homologs of rat C-CAM and the mouse Bgp species. These glycoproteins represent a family of cell-adhesion molecules. The mouse Bgp isoforms also act as receptors for the hepatitis viral capsid-protein. BGP is a member of the carcinoembryonic antigen (CEA) gene family, which belongs to the immunoglobulin supergene family, yet it displays restricted expression patterns and unique functions. Since the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…AP-2 consensus sequences, like the one immediately upstream of the USF-binding motif of cealO and bgpl, have been postulated to convey epithelial cellspecific expression of E-cadherin and cytokeratin genes [51]. Therefore, it is conceivable that the Myc-related transcription factor USF, although ubiquitously expressed [42], can confer expression in epithelial cells in conjunction with AP-2 or AP-2-like factors, which have also been demonstrated to bind, but further upstream in the BGP promoter [49] in comparison to the concensus sequence found in ceal0.…”
Section: Discussionmentioning
confidence: 99%
“…AP-2 consensus sequences, like the one immediately upstream of the USF-binding motif of cealO and bgpl, have been postulated to convey epithelial cellspecific expression of E-cadherin and cytokeratin genes [51]. Therefore, it is conceivable that the Myc-related transcription factor USF, although ubiquitously expressed [42], can confer expression in epithelial cells in conjunction with AP-2 or AP-2-like factors, which have also been demonstrated to bind, but further upstream in the BGP promoter [49] in comparison to the concensus sequence found in ceal0.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] These genes do not contain TATA or CAAT boxes but do contain potential binding sites for basal and regulatory transcriptional elements. Using a gel-shift assay, Hauck et al 33 have shown that nuclear factors including upstream stimulatory factor, hepatic nuclear factor-4, and an activator protein-2-like molecule can bind to the human C-CAM promoter region. However, it is not clear whether these transcription factors are involved in the regulation of C-CAM gene expression during carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms regulating CEACAM1 expression are poorly understood and the transcription factors described to regulate its promoter are distinct between rat and human species (Hauck et al, 1994;Najjar et al, 1996). The previously described luciferase reporter containing the functional 3.1 kb CEACAM1 human promoter (Hauck et al, 1994) (p3.1sluc) was used to study the regulation by SOX9.…”
Section: Sox9 Physically Binds To the Human Ceacam1 Promotermentioning
confidence: 99%